The effect of early age feed restriction on subsequent response to high environmental temperatures in female broiler chickens - Zulkifli, I.; Che Norma, M.T.; Israf, D.A.; Omar, A.R. (Poultry Science Association, 2000)
This study was conducted to determine whether early age feed restriction improves heat tolerance in female broiler chickens. Chicks were brooded for 3 wk and then maintained at 24 ± 1 C. On Day 0, chicks were assigned to one of four feeding regimens; each regimen was applied to four cages of chicks. The feeding regimens were 1) ad libitum feeding (ALF); 2) 40% feed restriction at 4, 5, and 6 d of age (F40); 3) 60% feed restriction at 4, 5, and 6 d of age (F60); and (4) 80% feed restriction at 4, 5, and 6 d of age (F80). From 35 to 41 d of age, all birds were exposed to 38 ± 1 C for 2 h/d. Serum concentrations of glucose were elevated by the heat challenge, but were not affected by the feeding regimen. The heat treatment resulted in hypocholesteremia among ALF and F80 chicks, whereas the concentrations increased and remained constant in the F60 and F40 birds, respectively. Subjecting chicks to F60 improved growth and survivability and reduced heterophil to lymphocyte ratios (H/L) in response to the heat treatment as compared with the ALF and F80 regimens. The survivability rate and H/L of F40 chicks were similar to those attained by chicks on other regimens. Newcastle disease antibody titer of ALF birds declined with duration of heat treatment. It is concluded that the F60 regimen is beneficial for alleviating, at least in part, the detrimental effects of heat stress in female broiler chickens.